Rugosidade superficial de ligas com alto conteúdo de cobre, em função do aquecimento acima da temperatura de fusão. - Bombonatti, P. E.; de Barros, L. E.; Scaranelo, R. M.; Pellizzer, A. J. (My University, 1990)
Being the surface roughness a fundamental property in the fit of the castings, it was determined the roughness of 5 high-copper casting alloys, according to the heating over their melting temperature. That way, the specimens made with smooth plastic in the shape of a rectangular plate, 2 mm x 7 mm x 11 mm were invested into a cristobalite investment. After heating and elimination on the plastic, the molds were filled by 3 g of molten alloy, casted in a electrical casting machine at the casting temperature at 25 degrees C and 50 degrees C overheating. The surface roughness was measured in a roughness analyser, Talysurf. As a result, it was verified that there is a variation of surface roughness among the alloys tested, and the heating of the alloys until 50 degrees C over the melting temperature does not interfere in the roughness.
Surface roughness of high copper alloys as a function of heating above casting temperature
Keywords: copper; dental alloy; denture; surface property; temperature; Copper; Dental Alloys; Dental Casting Technique; English Abstract; Support, Non-U.S. Gov't; Surface Properties; Temperature